Exploring the Intricacies of Encephalocele Case in Pregnancy: Unraveling Risk Factors, Diagnostic Difficulty, and Implications for Maternal and Fetal Health - Martani, Rizky Alamsyah; Santoso, Dhanny Primantara Johari (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Encephaloceles are a type of neural tube defect that carries a significant risk of death and health complications. Ultrasonography can be utilized for the early detection of encephaloceles starting from 11 weeks of gestation. This case report describes the diagnosis of an occipital encephalocele using ultrasonography during the third trimester of pregnancy and the subsequent monitoring of the condition until delivery. This report serves as a reminder of the potential implications and the importance of ongoing research in prenatal diagnosis of encephalocele to improve diagnostic and therapeutic strategies.Case Report: A 23-year-old woman, gravida 2, para 1 (G1P0A0), presented with lower abdominal pain without uterine contractions at 38 weeks of pregnancy, was consulted in the Department of Obstetrics and Gynecology of Slamet General District Hospital. She did nine antenatal visits; and three were performed through ultrasonography by a general practitioner. The occipital posterior defect was visualized with protruding mass consistent with an encephalocele during the third trimester when she was admitted to Slamet General Hospital Garut. A baby born by cesarean section with an encephalocele died three hours later.Discussion: Encephaloceles can be detected using two-dimensional (2D) and three-dimensional (3D) sonography as early as 11 weeks; however, most instances are typically diagnosed during the second trimester. Using advanced imaging technology and skilled sonographers, an encephalocele can be diagnosed at 14 weeks.Conclusion: Prenatal screening through ultrasonography and other advanced imaging techniques plays a significant role in identifying encephalocele prenatally. Understanding potential risk factors, including genetic predispositions and environmental influences, is important to better counsel patients on preventive strategies.Eksplorasi Kasus Kehamilan dengan Ensefalokel : Faktor Risiko, Kesulitan Diagnostik, dan Implikasi untuk Kesehatan Ibu dan JaninAbstrakPendahuluan: Ensefalokel adalah jenis cacat tabung saraf yang membawa risiko kematian dan komplikasi kesehatan yang signifikan. Ultrasonografi dapat digunakan untuk deteksi dini ensefalokel mulai dari usia kehamilan 11 minggu. Laporan kasus ini menjelaskan diagnosis ensefalokel oksipital menggunakan ultrasonografi selama trimester ketiga kehamilan, dan pemantauan kondisi selanjutnya hingga persalinan. Laporan ini menjadi pengingat pada implikasi potensial dan pentingnya penelitian yang sedang berlangsung dalam diagnosis ensefalokel prenatal untuk meningkatkan strategi diagnostik dan terapeutik.Laporan Kasus: Seorang wanita berusia 23 tahun, gravida 2, para 1 (G1P0A0), datang dengan keluhan nyeri perut bagian bawah tanpa kontraksi uterus pada usia kehamilan 38 minggu ke Departemen Obstetri dan Ginekologi di RSUD Slamet Garut. Pasien telah menjalani sembilan kali perawatan antenatal, tiga di antaranya dilakukan dengan ultrasonografi oleh dokter umum. Defek posterior oksipital divisualisasikan dengan massa yang menonjol konsisten dengan encephalocele pada trimester ketiga ketika admisi di RSUD Slamet Garut. Bayi lahir melalui operasi seksio sesarea dengan klinis encephalocele lalu meninggal tiga jam kemudian.Diskusi: Encephalocele dapat dideteksi dengan sonografi dua dimensi (2D) dan tiga dimensi (3D) sejak usia 11 minggu, namun sebagian besar kasus biasanya didiagnosis selama trimester kedua. Encephalocele dapat didiagnosis pada usia 14 minggu menggunakan teknologi ultrasonografi, tetapi deteksinya didasarkan oleh kemampuan operator. Kesimpulan: Skrining prenatal melalui ultrasonografi dan teknik pencitraan canggih lainnya memainkan peran penting dalam mengidentifikasi ensefalokel prenatal. Memahami faktor risiko potensial, termasuk faktor genetik dan lingkungan adalah penting untuk memberikan konseling yang lebih baik kepada pasien tentang strategi pencegahan.Kata kunci: Counseling, Diagnosis, Occipital Encephalocele, Risk Factors